2018
DOI: 10.4103/jips.jips_289_17
|View full text |Cite
|
Sign up to set email alerts
|

A clinical assessment of the volume of interproximal papilla after definitive prosthesis around immediate and delayed loading implants placed in the maxillary esthetic zone: An in vivo study

Abstract: The interpretation of clinical papilla is a difficult task since many different clinical situations can be encountered while studying single tooth implant restorations. The single tooth implant restoration is a specific entity; the distance between the mesial and the distal side of one implant is never the same. Therefore the present study analysed the papilla as a unit and focused on the vertical fill related to the implant and adjacent teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
1
0
1
Order By: Relevance
“…These findings were supported by a study done by Grossberg et al (2001), 45 in which four patients out of twelve showed complete papilla fill in between the implants. Also, Nariman et al (2018)'s 46 study found that both mesially and distally, the conventional group (Mesial side = 1.78 and distal side = 1.89) showed better papilla fill than the immediate group (mesial side = 1.20 and distal side = 1.30) which is in contrast to our study. Lee et al (2005) 47 showed that the soft tissue height in between two adjacent implants was 3.3 AE 0.5 mm.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings were supported by a study done by Grossberg et al (2001), 45 in which four patients out of twelve showed complete papilla fill in between the implants. Also, Nariman et al (2018)'s 46 study found that both mesially and distally, the conventional group (Mesial side = 1.78 and distal side = 1.89) showed better papilla fill than the immediate group (mesial side = 1.20 and distal side = 1.30) which is in contrast to our study. Lee et al (2005) 47 showed that the soft tissue height in between two adjacent implants was 3.3 AE 0.5 mm.…”
Section: Discussioncontrasting
confidence: 99%
“…Lee et al (2005) 47 showed that the soft tissue height in between two adjacent implants was 3.3 AE 0.5 mm. This is in accordance with the study done by Rushad Hosi et al, 46 who also stated that inflammation can lead to false assessment of papillary fill.…”
Section: Discussionsupporting
confidence: 92%